Manno-oligosaccharides as a promising antimicrobial strategy: pathogen inhibition and synergistic effects with antibiotics - Asbury, Rachel E.; Saville, Bradley A. (Frontiers in Microbiology, 2025)
Infections caused by pathogenic bacteria pose a significant health challenge to humans and animals, especially given the rising incidence of antimicrobial resistance. Addressing this challenge has resulted in initiatives seeking alternatives to traditional antibiotics. Manno-oligosaccharides (MOS) exhibit pathogen-binding properties, due to their ability to prevent bacterial adhesion to epithelial cells, such as those within the urinary tract and intestinal epithelium. This suggests that MOS could offer a promising alternative to antibiotics. In this study, we explore the ability of various β-MOS products to inhibit the growth of Escherichia coli, Klebsiella pneumoniae, Listeria monocytogenes, and Streptococcus mutans, in addition to their ability to render antibiotics more effective. Inhibition profiles were distinct for each bacterial strain and differed according to β-MOS structure. Antibiotics were significantly potentiated by MOS in some cases, such as ceftazidime against K. pneumoniae. This research shows the role of carbohydrate structure in the anti-bacterial properties of non-digestible oligosaccharides such as MOS and positions MOS as a promising strategy in the treatment of bacterial infections.